Pelaksanaan, Upaya Peningkatan, Kendala dan Solusi pada Sistem Pendaftaran Online di Rumah Sakit - Tria Sukma Witungga; Sentot Imam Suprapto; Eva Agustina (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Wilujeng Kediri Hospital implements an online registration system to improve the quality of registration services, increase patient and family satisfaction, as well as the effectiveness and efficiency of outpatient/polyclinic services. The problems that occur are the ineffectiveness of the online outpatient registration system, namely cancellation of registration without confirmation, cancellation of registration with confirmation, increasing workload for officers to delete registration history and officers' working time becoming inefficient. The aims of this research are exploring the implementation, analyze efforts to improve the online registration system, and exploring obstacles and solutions in implementing the online registration system at Wilujeng Kediri Hospital. The research uses descriptive qualitative research methods with collection techniques using interviews, observation and documentation. The data analysis process includes data reduction, data presentation and drawing conclusions. The research results showed that there were two online registration systems implemented at Wilujeng Kediri Hospital that used applications and also used WEB, which can be accessed by existing patients who already have a medical record number. New patients who do not have a medical record number cannot register online. Patients who want to be examined can register on the Android application or on the web with the procedures that have been socialized. Wilujeng Kediri Hospital has an SOP for online patient registration and the hospital has implemented an online registration service in accordance with Standard Operating Procedures (SOP). This standard contains procedures on how staff will serve patients who register online. The hospital implements online registration of outpatients in accordance with the procedures in the standard operating procedures (SOP). The computer equipment for online registration is in adequate condition. In implementing online registration, there is always education from the hospital marketing team. When patients are still confused, especially the elderly, they need assistance from family or other people who understand online registration. The hospital has provided online registration education to patients or hospital customers. However, patients still need adaptation in using the online registration system.